Метаболички профил кај млечни крави од различни категории - Улчар И., Целеска Ирена, Илиевска Ксенија, Митров Д., Џаџовски И. (Macedonian Veterinary Review, 2008)
Knowing the values of the metabolic profile is important for prevention of so-called "production diseases" which have significant negative impact on the milk production. The aim of these investigations was determination of the metabolic profile and its referent values in the diary cows in several farms. Investigations included four categories of diary cows: pregnant heifers, cows in early lactation, cows in late lactation and dry cows. Discussion explains both significant differences of values of some parameters (glucosis, total proteins, urea, creatinine, AST, GGT) in different groups of animals which were investigated and significant correlations between some parameters (glucosis, total protein, albumin, calcium, phosphorus, urea, creatinine, cholesterol, triglycerids, AST, GGT) within each of groups of animals. The values gained with our investigations were compared with the referent values. It was found that cows included in our investigations were good metabolic profile, although their values were in some degree different from the referent values. Cows which were in lactation, especially the early lactation, had disposition of development of energy-protein deficit, but the disposition to calcium deficit was low.